The Theme of Loneliness and Isolation in Sherwood Anderson's Fiction - Segar, Ali Mohammed (Al-Adab Journal, 2015)
The aim of this research is to study the American writer Sherwood Anderson( 1876-1941 ) and his contribution in the American fiction in one of its most remarkable phases : that period of change and literary experimentalism that occurred after the First World War. In this period a new passion and consciousness comes into American writing .It is also thought of as a classic era of materialism, and business - ethics which the writers regularly condemned and expatriated themselves from it. The sense of loneliness and isolation is apparently depicted in Anderson's writings as a clear reflection of the general sense of American society at that time with the spread of commercial and industrial tendencies. The research tries to shed light on this theme in Anderson's major selection of short stories Winesburg, Ohio(1919) as well as in other works like The Triumph of the Egg (1921) and his novel Poor White(1920)